Why and how back pain interventions work: What can we do to find out? - Mansell, G.; Kamper, S.; Kent, Peter (Bailliere Tindall, 2013)
Mediation analysis is a useful research method that potentially allows identification of the mechanisms through which treatments affect patient outcomes. This chapter reviews the theoretical framework, research designs and statistical approaches used in mediation analysis. It describes what can be learnt from previous mediation research, much of which has investigated mediating factors of psychosocial interventions in other health conditions. It also summarises the few treatment-mediation studies of psychosocial interventions conducted in back pain. This chapter shows that there is emerging evidence about the role of some psychological factors as potential treatment mediators, such as self-efficacy and catastrophising. Mediation analysis can equally be applied to non-psychological factors. Pre-planned and appropriately conducted mediation analysis in adequately powered clinical trials would be a step forward in understanding treatment effects in back pain and improving patient management.